The Role of Dental Assistants & Technicians in Modern Dental Practices: Responsibilities and Challenges - Shaher Dakhel Almutairi1, Rami Abdullah Alhowshani2, Bandar Saleh Albadrani3, Suleiman Saad Al-Kathiri4, Mohammed Salem Mohsen Alharbi5 , Asma Ghanim Al-Harbi 6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Dental assistants and technicians are indispensable members of modern dental practices, adapting to evolving roles influenced by technological advancements and patient care needs. Their expanding responsibilities encompass infection control, patient education, practice administration, digital dentistry, and collaboration with dentists. Challenges such as heavy workloads, technology competency, regulatory compliance, communication skills, and professionalism are also discussed. Effective training, continuing education, and supportive workplace policies are essential for assistants and technicians to thrive in their roles and deliver quality, patient-centered dental care. This overview provides insights into the crucial contributions of dental assistants and technicians to contemporary dental practice, emphasizing their role in ensuring optimal treatment outcomes and enhancing the patient experience